SNF 심지층 처분장 내 반응성 가스-지하수-벤토나이트 시스템의 장기적 지화학 반응 모델링 - 신대현(Daehyun Shin), 박소영(Soyoung Park), 전소영(Soyoung Jeon), 양민준(Minjune Yang), 이민희(Minhee Lee) (자원환경지질, 2025)
One of the critical barriers in the DGR (deep geological repository) is the buffer, which reduces stress on the storage canister and delays the release of radioactive nuclides. Bentonite is well known for a potential buffer material due to its low hydraulic conductivity, high swelling capacity, and strong adsorption properties for radionuclides. In this study, the geochemical reaction modeling was conducted to evaluate the long-term effects of reactive gases (CO2 and H2S) on bentonite (a candidate buffer material for the domestic SNF (spent nuclear fuel) repository). As a simulation code for the modeling, the PHREEQC version 3.7.3 was used with the LLNL (Lawrence Livermore National Laboratory) thermodynamic database for a simulation period of 100,000 years. Reaction conditions were designed for the reactive gas-groundwater-bentonite system, based on groundwater quality data from the KURT (KAERI underground research tunnel) site and mineralogical data of bentonite. Equilibrium reaction modeling results in the gas-groundwater system supported that the groundwater inflow from the surrounding bedrock led to an acidic and aerobic environment in the bentonite pore spaces due to the dissolution of residual atmospheric gases (O2 and CO2). Based on the equilibrated water quality data, the kinetic reaction modeling for bentonite interactions with aerobic microbial respiration was performed. From results of the modeling, oxygen in groundwater was completely depleted after approximately 5,190 years, transitioning the system to the anaerobic condition. Montmorillonite and calcite were identified as the primary dissolving minerals in Bentonil-WRK, exhibiting mass losses of 0.024% and 0.37%, respectively. Secondary precipitated minerals by the geochemical reaction included kaolinite, dolomite, chalcedony, and pyrite. Over the 100,000 year simulation period, the reactive gases resulted in a 0.0029% decrease in mineral volume of Bentonite and a 0.0043% increase in pore volume. It suggested that the long-term stability of the buffer material in the SNF repository may be affected by geochemical reactions induced by reactive gas generation. 본 연구에서는 반응성 가스인 CO2 및 H2S 가스가 지화학 반응을 통해 국내 사용후핵연료 심지층 처분장 내 완충재 물질로 고려되고 있는 벤토나이트에 미치는 장기적인 영향을 평가하기 위한 지화학 반응 모델링을 수행하였다. 지화학 반응 모델링 코드는 PHREEQC version 3.7.3을 사용하였으며, LLNL (Lawrence Livermore National Laboratory) 열역학 데이터 베이스를 활용하여 100,000년 동안의 지화학 반응을 모사하였다. 본 지화학 반응 모델링은 반응성 가스-지하수-벤토나이트 시스템에서 수행되었으며, KURT (KAERI underground research tunnel)에서 채취한 지하수 수질 데이터와 벤토나이트의 광물학적 데이터를 사용하였다. 본 연구에서 수행된 지화학 반응 모델링은 처분장 초기 환경을 모사한 가스-지하수-벤토나이트 평형 반응 모델링을 수행하였으며, 평형 반응 모델링의 수질 결과를 바탕으로 동역학 반응 모델링을 수행하였다. 가스-지하수 평형 반응 모델링은 지하 처분장의 저장공 굴착 후 초기 조건을 고려하여 대기압 조건에서 수행되었으며, 동역학 반응 모델링의 경우 지하수 내 미생물 반응에 의해 지하수에 용존하는 O2를 소비하는 유산소 환경과, 무산소 환경에서 SO42-를 소비하는 환경을 모사하였다. 평형 반응 모델링 결과, 벤토나이트 공극 내 잔류하는 대기 가스(O2와 CO2)에 의해 지하수는 산성 및 호기성 환경으로 전이되 었다. 반응성 가스-지하수-벤토나이트 동역학 반응 모델링 결과, 미생물 호흡에 의해서 지하수 내 용존 O2와 SO42-를 반응 시간 순서대로 소비하며 CO2와 H2S 가스를 생성하였다. 초기 유산소 환경에서 지하수 내 용존 O2는 약 5,190년 후 완전히 소비되어 혐기성 환경으로 전환되었다. 동역학적 지화학 반응에 의해 벤토나이트 구성 광물 중, 몬모릴로나이트(montmorillonite)와 방해석(calcite) 등이 대표적인 용해 광물로 밝혀졌고, 용해반응에 의해 벤토나이트 내 몬모릴로나이트(montmorillonite)와 방해석 (calcite)의질량은각각 0.024%와 0.37%가감소하였으며, 침전반응에의해고령석(kaolinite), 백운석(dolomite), 칼세도니(chalcedony), 황철석(pyrite)이 생성되었다. 100,000년 기간의 장기 반응 모델링 결과, 반응성 가스에 의해서 벤토나이트 내 광물의 부피는 0.0029%가 감소하였으며, 공극의 부피는 0.0043%가 증가하였다. 이러한 결과는 완충재 내 반응성 가스의 지화학 반응이 완충재의 특성 변화를 야기하여 SNF 처분장 내의 장기적 안정성에 영향을 미칠 수 있음을 시사한다.